Final answer:
To find f(-3), substitute -3 for x in f(x) = -x^2 + 7x - 13.
Step-by-step explanation:
A mathematical expression is a combination of numbers, variables, and operations (such as addition, subtraction, multiplication, and division) that represents a mathematical relationship. It can be as simple as "2 + 3" or more complex, involving variables and functions.
To find f(-3), we need to substitute -3 for x in the given function f(x) = -x^2 + 7x - 13. This gives us:
f(-3) = -(-3)^2 + 7(-3) - 13
= -9 + (-21) - 13
= -9 - 21 - 13
= -43
Therefore, f(-3) = -43.